Empowerment of 5th Grade Teaching Campus Students in Improving the Reading and Writing Literacy Ability of Students at UPTD SDI Perawea - Wea*, Dorotea Emirensiana; Dopo, Ferdinandus Bate; Dopo, Florentianus (Riwayat: Educational Journal of History and Humanities, 2024)
I took this service activity program with the title "Teaching Campus Student Empowerment Program in Improving Students' Reading and Writing Literacy at UPTD SDI Pwrawea". aims to improve students' reading and writing literacy skills at UPTD SDI Perawea through reading literacy activities 15 minutes before learning, wall media activities and reading corners. To find out the problems that occurred, students from the 5th campus teaching program carried out AKM posting activities at the beginning of the assignment. Based on the results of AKM activities at the beginning of campus teaching program activities, results were quite low, this was due to students' lack of awareness of the importance of reading and writing literacy. This service program was carried out together with field supervisors (DPL) and campus students teaching class 5 for 4 months 20 February-16 June 2023. The subjects of this service activity were class 5 students with a total of 10 students. The implementation of this service activity goes through several stages, namely planning, implementation and evaluation. The results of this service activity were successful in improving the reading and writing literacy skills of grade 5 students by implementing student reading and writing literacy at UPTD SDI Perawea